The Relationship Between Social Sciences and Social Sciences: Resources and Energy - Eka Yusnaldi; Dwi Retno Anjani; Asyura Asyura; Jihan Ramadhani Faizera; Yulinda Ritonga; Viola Putri (Pusdikra-Publishing.com, 2024)
The aim of this research is to find out the relationship between social sciences and social sciences and society. Social sciences can play an important role in social education, because they provide the opportunity to understand relationships between humans more systematically and be able to apply them in everyday life. Social education is broader than social science and is not limited to one area of the curriculum, or to education within schools. The social sciences that have made many contributions to Social Sciences are Geography, History and Pancasila Moral Education. Besides that, a lot of material is needed from Anthropology, Sociology, Political Science, Economics, Psychology, Philosophy and sometimes even Natural Science.